Artificial Intelligence-Based Arabic Language Learning: A Systematic Study of the Development and Challenges of Pedagogical Innovation - Yazid Hady; Siti Nurul Azkiyah; Muhbib Muhbib; Maswani Maswani (CV FOUNDAE, 2026)
The significant growth rate of artificial intelligence (AI) in virtual learning has significantly changed learner-technology interactions, leading to pedagogical, cognitive, and ethical implications in terms of Arabic language learning. The study aims to explore the research trends and implementation difficulties associated with integrating AI in Arabic language learning through a Systematic Literature Review (SLR). The study used a systematic search on Scopus and Google Scholar databases using publications within 2023 to 2025, with 200 publications identified. Through a PRISMA-based literature review, 15 peer-reviewed articles were identified as eligible for synthesis. The review was conducted through a thematic coding framework using Constructivist Theory, Knowledge Creation Theory, and DIKW hierarchy as a theoretical foundation. The study found that AI plays a significant role in improving reading, writing, listening, and speaking skills through adaptive feedback, conversational agents, text generation tools, and speech recognition tools. The patterns identified through this review indicate that there are challenges associated with integrating AI in Arabic language learning, such as limited Arabic linguistic resources, inaccuracies in AI-generated text, morphological, and syntactical errors, readiness, and dependency on AI tools by learners. The review established that AI has significant transformative potential in Arabic language learning with appropriate pedagogy, educator readiness, and appropriate use of technology.